PENDAMPINGAN BACA TULIS AL-QURAN UNTUK MEMBENTUK MASYARAKAT YANG BERJIWA ISLAMI DAN QUR'ANI DI DESA BLANKAHAN KABUPATEN LANGKAT - Mardiah; Sanggul Maharani Yessa; Syamsiah Nasution; Irhamuddin Siregar; Hadi Siswoyo (Perkumpulan Pendidikan Islam Anak Usia Dini Wilayah Sumatera, 2022)
This activity aims to provide assistance to the community and children of Blankahan village in an effort to form a society with an Islamic and Qur'anic spirit. The weak knowledge of reading and writing the Koran among children in Blankahan village, Dusun V, Kuala District, Langkat Regency, is a concern for STIT Al Washliyah Binjai lecturers who are carrying out PkM activities in the village. Apart from that, the lack of teaching staff who can teach reading and writing the Koran has resulted in a lack of ability to read and write the Koran among children in the village. Learning to read the Koran must be done from an early age as a provision for life in this world and the afterlife. The efforts made are by carrying out learning activities to read and write the Koran which are carried out regularly. Activities are carried out by involving the community in the surrounding environment.